Investigating the prospect of copper-histidine complex modified gold electrode for histidine and human serum albumin recognition - Kereković, Irena (Array, 2020)
Histidine monolayer was adsorbed on the surface of the gold electrode and further tailored with Cu2+ cation with the aim to investigate adsorption of histidine (His) and human serum albumin (HSA). Formation of the layer on the surface of the gold electrode was confirmed with quartz crystal microbalance. Binding of the His and HSA onto the modified electrode was successfully done for a wide range of tested concentrations. Electrode response was linearly proportional to the concentration of His and HSA with the correlation coefficients R2 = 0.9895 and R2 = 0.9952 respectively.